2015
DOI: 10.1017/ice.2015.254
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Carbapenem-Resistant Klebsiella pneumoniae Colonization and Infection among Long-Term Acute Care Hospital Residents

Abstract: Objective An improved understanding of carbapenem-resistant Klebsiella pneumoniae (CRKP) in long-term acute care hospitals (LTACHs) is needed. The objective of this study was to assess risk factors for colonization or infection with CRKP in LTACH residents. Methods A case-control study was performed at a university-affiliated LTACH from 2008 to 2013. Cases were defined as all patients with clinical cultures positive for CRKP and controls were those with clinical cultures positive for carbapenem-susceptible K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…The overuse of broad-spectrum antimicrobial agents and invasive procedures has led to an increase in the prevalence of drug-resistant K. pneumoniae and in the incidence of CRKP infection. 19,20 Our findings are consistent with those of other studies, which have reported a strong association between exposure to carbapenem agents and CRKP infection. 21,22 Carbapenem use may cause selective pressure on resistant microorganisms, thereby increasing the risk of infection.…”
Section: Dovepresssupporting
confidence: 92%
“…The overuse of broad-spectrum antimicrobial agents and invasive procedures has led to an increase in the prevalence of drug-resistant K. pneumoniae and in the incidence of CRKP infection. 19,20 Our findings are consistent with those of other studies, which have reported a strong association between exposure to carbapenem agents and CRKP infection. 21,22 Carbapenem use may cause selective pressure on resistant microorganisms, thereby increasing the risk of infection.…”
Section: Dovepresssupporting
confidence: 92%
“…In order to prevent colonization, the investigation of the clinical predictors and risk factors for rectal CPE colonization brooks no delay. A recently published case-control study demonstrated solid organ and stem cell transplantation, mechanical ventilation, fecal incontinence, and exposure in the prior 30 days to carbapenems, vancomycin, and metronidazole as independent factors associated with CRE colonization [32]. In this prospective case-control study, operation of bronchoscopy, urinary system diseases, and combined use of antibiotics were demonstrated to be independent associated with rectal CPE colonization in high-risk patients from the ICU and HSCT wards.…”
Section: Prevalence Of Positive Cre Colonization Among High-risk Patimentioning
confidence: 62%
“…This species is disseminated in healthcare settings via person-to-person contact, medical equipment, and contaminated environments [2, 3]. The emergence of multidrug-resistant K. pneumoniae is becoming an increasingly serious issue for clinical practice, largely related at the present time to isolates that express extended-spectrum β-lactamase (ESBL) enzymes that hydrolyze a broad spectrum of β-lactams [4, 5]. This is compounded by the emergence of K. pneumoniae that express carbapenemases such as KPC-type β-lactamase [57] and the recent detection of colistin-resistant K. pneumoniae due to the presence of the mcr-1 gene [8].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of multidrug-resistant K. pneumoniae is becoming an increasingly serious issue for clinical practice, largely related at the present time to isolates that express extended-spectrum β-lactamase (ESBL) enzymes that hydrolyze a broad spectrum of β-lactams [4, 5]. This is compounded by the emergence of K. pneumoniae that express carbapenemases such as KPC-type β-lactamase [57] and the recent detection of colistin-resistant K. pneumoniae due to the presence of the mcr-1 gene [8]. These resistance genes are carried on mobile genetic elements that facilitate their spread within and between bacterial species, a process that is likely to result in a rise in the number of K. pneumoniae infections that are very difficult to treat.…”
Section: Introductionmentioning
confidence: 99%